2005
DOI: 10.1021/ie0580349
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Diesel Oxidation Catalyst

Abstract: Optimization of hydrocarbon (HC) oxidation over a diesel oxidation catalyst (DOC) requires consideration of (i) HC gas diffusion into the catalyst layer, (ii) HC gas adsorption and desorption from catalyst sites, and (iii) kinetics of the oxidation reaction. We have already reported a brief modeling study that emphasized understanding HC storage and release from zeolitic sites within the DOC [Banno et al., SAE Tech. Pap. Ser. 2004-01-1430. In this study, more-detailed DOC modeling was attempted, using a precis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 10 publications
2
14
0
Order By: Relevance
“…Mutagenicity was slightly increased by the B100 exhaust (120 mg/plate) at high load mode M2 with a great increase in NO 2 concentration [ 23 ], which might be responsible for synthesizing even more genotoxic materials, nitro-PAH, under these conditions. Our results are similar to those from the different studies showing that changes depended mainly on engine load modes [ 34 , 62 , 63 ]. They suggested that high engine load increases NOx in the exhaust and NOx cannot effectively be reduced by a DOC, while high NOx levels lead to an increased formation of nPAH.…”
Section: Discussionsupporting
confidence: 92%
“…Mutagenicity was slightly increased by the B100 exhaust (120 mg/plate) at high load mode M2 with a great increase in NO 2 concentration [ 23 ], which might be responsible for synthesizing even more genotoxic materials, nitro-PAH, under these conditions. Our results are similar to those from the different studies showing that changes depended mainly on engine load modes [ 34 , 62 , 63 ]. They suggested that high engine load increases NOx in the exhaust and NOx cannot effectively be reduced by a DOC, while high NOx levels lead to an increased formation of nPAH.…”
Section: Discussionsupporting
confidence: 92%
“…The authors proposed that the DOC increases formation of direct acting mutagens under certain conditions by the reaction of NO X with PAH. 35 Therefore, the effectiveness of a DOC can depend on the engines, the fuels and the mode of operation. In fact, test cycles that simulate traffic conditions result in higher emission rates of products of incomplete combustion compared to tests at constant load mode, since at load changes the combustion is temporarily suboptimal due to an oxygen shortage.…”
Section: ■ Discussionmentioning
confidence: 99%
“…44−46 Combustion with formation of NO X may promote nPAH production. 35 3-NBA (3-nitro-7H-benz[d,e]anthracen-7-one) was identified as a prominent compound in extracts from diesel exhaust and ambient particles which showed very strong direct mutagenic and clastogenic effects in vitro. 47 It therefore served as a positive control for direct acting mutagenicity in the present investigation.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Consequently, CO tail-pipe emissions, decrease significantly with temperature. HC conversion efficiency also increases with temperature (Tanaka et al, 2005); however, the slope of conversion curves decreases at higher temperatures, indicating that there is an upper limit for this increase (Tanaka et al, 2005). HC tail-pipe emissions also decrease with temperature; however, the slope is lower than in the case of CO, indicating that temperature is more important in the case of CO oxidation than on the case of HC oxidation, as shown in Figures 1 and 2.…”
Section: Impact Of Average Exhaust Temperature and Doc Volume On Co Amentioning
confidence: 90%
“…For constant engine-out CO missions, tail-pipe HC emissions increase with HC engine-out emissions (Tanaka, 2005), even if conversion efficiency slightly increases, because engine-out HC emissions are much higher than the increase of the corresponding conversion. For constant engine-out HC emissions, HC oxidation is very little influenced by CO, as tail-pipe HC emissions remain practically constant with engine out CO emissions.…”
Section: Impact Of Co and Hc Engine-out Emissions On Co And Hc Convermentioning
confidence: 95%